A foraclusão do Nome-do-Pai e as dificuldades do psicótico no laço social: de um tratamento possível da psicose - Grecco, João Ezequiel (2015)
This thesis has the primary objective to characterize the difficulties of the psychotic in the social bond, depending on their particular way to confront (and deny) the castration of the Other: the foreclosure of the Name of the Father (Verwerfung). Look up the theoretical foundations established by Jacques Lacan to the understanding of psychosis, with the upper limit of the year 1958, when it was written the article "From a preliminary question at all possible treatment of psychosis" if a concept exceeds this limit, the only goal is its contextualization, which goes no further than the thesis proposes. From these fundamentals, seeks to demonstrate the thesis that it is the absence of significant Name of the Father in place of the Other that gives the specificity of his psychotic symptoms and the particularity of the conditions (and difficulties) of its relations with and the other with reality. It is intended, in addition, explore in depth the meaning of Lacanian conceptions about the conditions of a possible treatment of psychosis during the study period. This is a theoretical research in psychoanalysis, which includes a preliminary stage of literature of Freudian and Lacanian work (oral and written), including seminars and written to the aforementioned date. Therefore, to meet the thesis of the goals built three axes; Initial contributions of psychosis in Freud, Lacan's formulations about psychosis and considerations about a possible treatment of psychosis, the discussion of the results found the difficulty in psychotic insertion in the social bond, the routing of the psychotic treatment and the relationship the psychotic forward the demand of the Other